Identifikasi Jenis Lichen di Kawasan Objek Wisata Teluk Wang Sakti - Eastu Septine Andrea; Rozana Zuhri; Leni Marlina (BIOCOLONY, 2018)
This research was motivated by the lack of data on the types of lichen in the Teluk Wang Sakti Area and the research on the types of lichen in Merangin is very lacking. Lichen can be found in the Teluk Wang Sakti Area because it has natural conditions that support lichen growth and development. The purpose of this research was to find out and describe the types of lichen in Teluk Wang Sakti. This type of research used a qualitative descriptive research. The research method used was the method of reconassance (roaming). The location of the research was conducted in Teluk Wang Sakti and on the edge of Jl. Lintas Bangko-Kerinci. Lichen found in Teluk Wang Sakti is 60 species including 11 genera and 10 families : Parmotrema and Parmelia (Family Parmeliaceae),Graphis (Family Graphidaceae), Dichosporidium (Family Rosellaceae), Arthonia (Family Arthoniaceae), Dirinaria (Family Dirinariaceae), Cryptothecia (Family Cryptotheciaceae), Lecanora (Family Lecanoraceae), Megalospora (Family Megalosporaceae), Lepraria (Family Leprariaceae) and Caloplaca (Family Caloplacaceae). Teluk Wang Sakti Area has an average temperature of 27.9oC and 82.3% humidity. While on the edge of Jl. Bangko-Kerinci crossing around the factory has an average temperature of 42.2oC and humidity of 36%. The Teluk Wang Sakti Area is indicated to have better air quality compared to the edge of Jl. Bangko-Kerinci crossing around the factory, due to the lack of types of lichen found and the presence of Parmotrema sp. type of lichen used as a bioindicator of air pollution.